(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
The Effectiveness of a Psychological Counseling and Rehabilitation Program Combined with EMG Technique for the Adductor Muscles of the Thighs on Muscle Strength and Emotional Arousal in Injured Football Players